Audit of It Process Ai-02 CobIt in Academic Information System (Case Study on Several Vocational Higher education in Bandung) - SURYA, Rendra Trisyanto; KERIHI, Anthon Simon Yohanis; MURHABAN, Murhaban; HAQ, Ashanul (Journal of Governance, Taxation and Auditing, 2023)
The development of Information Technology (IT) allows the Academic Information System (SIAK) to become a central element in the management process of Higher Education, primarily Academic. On the other hand, the sophistication of IT in SIAK develops a variety of new risks (IT Risks) that accompany it if not managed properly. Therefore, the maturity level of SIAK management determines the performance of the academic activity process. In SIAK, the element that determines system performance is Application Software. The results of this study indicate that IT Process AI-02 (Procurement of Application Software) Vocational Higher Education in Bandung, as measured based on COBIT standards, is still at the 2.1 level. This means a part/function (management) already handles Software Procurement but is still "Repeatable but intuitive." Because it is managed sporadic and only refers to leadership policies with limited control over IT/SIAK. From the radar chart of the research results, it can be seen that the prominent role of IT Process AI-02 is the aspect (indicator) of "Approval," "Technical Support from Vendors," and focus on handling the problem of "data integration" because many universities are in the transition period from old IT to new IT. Other indicators (COBIT requirements) still need to be higher (meaning they have not become a concern) when the AIS procurement process is carried out.